OP0305 Type I IFN system activation in newborns exposed to ANTI-RO/SSA autoantibodies in utero. (15th June 2017) - Wahren, M; Hedlund, M; Thorlacius, GE; Ivanchenko, M; Kyriakidis, N; Rönnblom, L; Eloranta, M-L; Espinosa, A; Sonesson, S-E
Abstract : Background: Overexpression of type I IFN-stimulated genes has been demonstrated in both SLE and SS, and induction of IFNα production in plasmacytoid dendritic cells by immune complexes containing RNA and autoantibodies, including Ro/SSA and La/SSB autoantibodies, has also been shown. During pregnancy, these autoantibodies pass over the placenta to the fetus, but it is not know if an IFN-activation takes place also in the fetus. Objectives: In the present study, we investigated if the type I IFN system is activated in newborns exposed to anti-Ro/SSA autoantibodies in utero . Methods: Anti-Ro/SSA positive mothers and their babies as well as healthy controls were included in the study. Maternal and cord blood drawn at birth was immediately separated into plasma and PBMC. mRNA expression was analyzed by microarrays, cell surface markers were assessed by flow cytometry and circulating IFNα levels by DELFIA. Results: We observed increased expression of IFN-regulated genes and elevated plasma IFNα levels not only in anti-Ro/SSA positive women but also in their newborns, with maternal and fetal IFN scores showing a significant positive correlation (r=0.74, p=0.005). Increased expression of MHC class II was observed on CD14 + monocytes of anti-Ro/SSA antibody-exposed babies, suggesting cellular activation. Notably, the IFN score of babies born to mothers receiving immunomodulatory treatment was similar to that of controls. Conclusions: We demonstrate for the first time that anti-Ro/SSA antibody-exposed babies at risk for neonatal lupus have a pre-activated immune system with an IFN signature, elevated plasma IFNα, and increased MHC class II expression on circulating monocytes. Our data also suggest that maternal immunomodulatory treatment may modulate the IFN activity in the baby. Disclosure of Interest: None declared